Propofol emulsification in Intralipid and SMOFlipid: A promising alternative in response to future shortages - Maxime Murphy; Mihaela Friciu; Valérie Gaëlle Roullin; Grégoire Leclair (PLoS ONE, 2025)
Introduction The Covid-19 pandemic has intensified shortages in various pharmaceutical products, notably injectable propofol in lipid emulsion form. Its demand surged sharply due to its critical role in intubating patients with respiratory distress during the pandemic, exposing vulnerabilities in the supply chain for this essential product. Objectives This project aims to develop an alternative formulation to commercially available propofol products and to evaluate its stability through a detailed study. Methods Two lipid emulsions commonly used for intravenous nutrition, Intralipid 20% and SMOFlipid 20%, were selected as diluents for pure propofol due to their composition’s similarity to DIPRIVAN, the standard propofol product. We developed and validated an HPLC method for quantifying propofol and employed an optimized laser diffraction technique to measure particle size. Additionally, we assessed the pH of the formulations. Results The preparation method demonstrated repeatability and homogeneity. Stability studies revealed that the propofol concentrations remained close to the target of 10 mg/mL (1%). Although particle sizes were larger compared to DIPRIVAN, they were consistent with those of the lipid emulsions before propofol addition. The pH of the formulations remained stable throughout the study period. Conclusions The developed propofol emulsion formulations met USP standards for all tested parameters over a period of at least 7 days, indicating that these alternatives are a viable and stable substitute for commercial propofol products.